Wellbeing in Educational Contexts - Carter, Susan; Andersen, Cecily (Open textbook library., 2019)
This text endeavours to focus on wellbeing promotion in educational contexts as schools and other educational contexts play a pivotal role in teaching students about nonviolence, promoting understanding of diversity, endowing people with a shared purpose and meaning and the skills and behaviours to create a more inclusive, healthy, and positive future.